2021
DOI: 10.1016/j.jamda.2021.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Mortality Risk in Older Hospitalized Persons With COVID-19: A Comparison of the COVID-19 Mortality Risk Score with Frailty and Disability

Abstract: Objectives: To assess the association of pre-morbid functional status [Barthel Index (BI)] and frailty [modified Frailty Index (mFI)] with in-hospital mortality and a risk scoring system developed for COVID-19 in patients !75 years diagnosed with COVID-19. Design: Retrospective bicentric observational study. Setting and Participants: Data on consecutive patients aged !75 years admitted with COVID-19 at 2 Italian tertiary care centers were collected from February 22 to May 30, 2020. Methods: Overall, 221 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
(28 reference statements)
1
14
2
1
Order By: Relevance
“…The outcomes that have been analyzed ranged from ICU admission and respiratory failure to mortality. In accordance with our findings, age was identified as a significant predictor across studies [ 23 28 , 30 37 , 39 ]. If its influence was quantified via cutoff values, these mostly ranged between 60 and 75 years [ 25 , 26 , 30 32 , 36 , 37 ] and thus were not markedly different from the value of 70 years which we found adequate for all outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…The outcomes that have been analyzed ranged from ICU admission and respiratory failure to mortality. In accordance with our findings, age was identified as a significant predictor across studies [ 23 28 , 30 37 , 39 ]. If its influence was quantified via cutoff values, these mostly ranged between 60 and 75 years [ 25 , 26 , 30 32 , 36 , 37 ] and thus were not markedly different from the value of 70 years which we found adequate for all outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…for in-hospital mortality Fallon et al [ 47 ] Ireland 25.03.2020–24.04.2020 R/C CFS R/P+ > 65y PCR 86 29 77 n/r Frailty diff. for 30-day mort Fumagalli et al [ 48 ] Italy 22.02.2020–30.05.2020 R/C mFI R > 75y Clin 221 97 82 78–86 134 (60.6) In-hospital mortality Gilis [ 49 ] France 03.03.2020–25.04.2020 P/C CFS P > 75 PCR 186 56 85.3 5.78 92 (49.5) 30-day mortality, ICU admission, laboratory findings, symptoms, delirium, treatment Hewitt [ 50 ] UK, Italy 27.02.2020–28.04.2020 P/C CFS P+ > 18 PCR or Clin 1564 425 74 61–83 903 (57.7) In-hospital mortality; LOH Hoek [ 51 ] …”
Section: Resultsmentioning
confidence: 99%
“…Two studies presented data on mortality in association with a modified frailty index (mFI) [ 48 , 56 ]. Fumagalli et al included 221 patients aged 75 or older from two centres [ 48 ]. 44.3% of deceased patients were frail in contrast to 29% in survivors.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the group with older age and functional dependency showed a mortality risk 10 times higher than their counterparts [ 24 ]. In another experience involving ≥ 75 years patients, pre-infection disability and frailty significantly improved the accuracy of prognostic models, when added to clinical variables commonly used for younger individuals [ 25 ]. Further, in accordance with the existing literature [ 26 ], we found that women not needing oxygen support had the lowest mortality rate .…”
Section: Discussionmentioning
confidence: 99%